Efforts of Islamic Religious Education Teachers in Improving Student Learning Motivation in High School - Al Ghazali Yaspan, Muhammad Abdul Fatah; Revi Septiana (Global Action and Education for Society, 2025)
When motivation is applied properly, students will be more focused on receiving the material, reducing the habit of postponing assignments, and being more confident in understanding and practicing Islamic teachings. This study aims to analyze the learning motivation of class X.5 students in the subject of Islamic Religious Education (PAI) at SMA Negeri 1 Rengat and the efforts made by PAI teachers in increasing this motivation. The research method used is qualitative descriptive with data collection techniques through observation and interviews. The results of the study show that the learning motivation of class X.5 students in PAI lessons can be categorized as good, although there are some students who are less focused on learning. PAI teachers play an important role in increasing student motivation by using interesting and varied learning strategies, as well as differentiated learning that is tailored to student needs. In addition, giving gifts or rewards in the form of praise, assignment dispensation, and other prizes are effective in increasing students' enthusiasm and motivation to learn. This study concludes that students' learning motivation can be improved through appropriate learning strategies and rewards that motivate students to perform better.